Thermodynamic properties of Anacardium humile St. Hil. (cajuzinho-do-cerrado) achenes - Barbosa, Karine Feliciano (2018)
The cajuzinho-do-cerrado is a native species of the cerrado of great potential of use and is threatened of extinction. The aim of this study was to determine and evaluate the thermodynamic properties of Anacardium humile St. Hil. achenes from the different hygroscopic equilibrium points according to the moisture content. To obtain the isotherms, the indirect static method was used at temperatures of 10, 20, 30 and 40 °C and for moisture contents of 13.4, 11.1, 8.7 and 5.3% dry basis (db). The Copace model was used to describe the hygroscopic equilibrium of the achenes. The thermodynamic properties are influenced by the moisture content because the latent heat of vaporization of the water of the achenes increases with the decrease in the equilibrium moisture content, varying between 3,035.63 and 2,510.80 kJ kg-1 for moisture contents of 4.51 to 13.4% db, respectively. The differential enthalpy and entropy are closely related to the moisture content of the achenes. The isokinetic temperature of 304.67 K denotes the linear chemical compensation between the differential enthalpy and entropy of the Anacardium humile St. Hil. achenes, and the desorption process is controlled by enthalpy.